Influence of fertilizers and of the autumn tillage method on potato yield and phytopathologiс characteristics of tubers - V. I. Titova; E. T. Akopdzhanyan (Аграрная наука Евро-Северо-Востока, 2021)
The field experiment on identifying differences in the effect of the herbicide and foliar feeding of plants with liquid nitrogen fertilizer (UAN-32) against the background of autumn tillage with a cultivator or plow on potato yield and phytopathologic characteristics of tubers during storage was carried out in 2019-2020 in the Nizhny Novgorod region. The experiment was laid on sod-podzolic sandy loamy soil in production conditions on two varieties of potato ‒ the super-early Сolomba variety and the medium-early Innovator variety grown for seeds. The variants under study were surface application of the soil herbicide Gezagard in a tank mixture with UAN-32 and foliar feeding of plants with UAN-32 (N42) during the growing season against the background of N42P42K169 (calcium chloride in autumn + ammonium nitrate phosphate in spring). The results indicate that the background fertilization provides the yield of Colombа variety potato of 20.7-29.0 t/ha, the Innovator variety – 17.4-23.1 t/ha. The use of the herbicide is more effective during autumn tillage with a cultivator, providing an increase in yield of 28-37 % on both potato varieties, feeding of plants with UAN-32 contributes to an increase in yield (8-10 %) only on the Сolomba variety. Plowing the soil for potatoes helps to avoid the pest damage of tubers and to reduce their susceptibility to rhizoctonia by 6-27 %, to wet rot ‒ up to 55 %. In general, it has been established that due to autumn plowing with fertilization at a dose of N42P42K169, it is possible to obtain an increase in potato yield exceeding the increase provided both by herbicides and the use of foliar feeding of potatoes.